Mutation of the rice TCM12 gene encoding 2, 3‐bisphosphoglycerate‐independent phosphoglycerate mutase affects chlorophyll synthesis, photosynthesis and chloroplast development at seedling stage at low temperatures. (1st April 2019) - Lin, D.; Zhang, L.; Mei, J.; Chen, J.; Piao, Z.; Lee, G.; Dong, Y.
Abstract: Glycolysis is a central metabolic pathway that provides energy and products of primary metabolites. 2, 3‐Biphosphoglycerate‐independent phosphoglycerate mutase (iPGAM) is a key enzyme that catalyses the reversible interconversion of 3‐phosphoglycerate (3‐PGA) to 2‐phosphoglycerate (2‐PGA) in glycolysis. Low temperature is a common abiotic stress in rice production. However, the mechanism for rice iPGAM genes is not fully understood at low temperature. In this study, the rice mutant tcm12, with chlorosis, malformed chloroplasts and impaired photosynthesis, was grown at a low temperature (<20 °C) to the three‐leaf stage, while the normal phenotype at 32 °C was used. Chlorophyll fluorescence analysis and transmission electron microscopy were used to examine features of the tcm12 mutant. The inheritance behaviour and function of TCM12 were then analysed thorough map‐based cloning, transgenic complementation and subcellular localisation. The thermo‐sensitive chlorosis phenotype was caused by a single nucleotide mutation (T→C) on the fifth exon of TCM12 (LOC_Os12g35040) encoding iPGAM, localised to both nucleus and membranes. In addition, TCM12 was constitutively expressed, and its disruption resulted in down‐regulation of some genes associated with chlorophyll biosynthesis and photosynthesis at low temperatures (20 °C). This is the first report of the involvement of rice iPGAM gene in chlorophyll synthesis, photosynthesis and chloroplast development, providing new insights into the mechanisms underlying early growth of rice at low temperatures.